Leadership Behaviour and Role Stressors among Primary School Teachers in Kenya (International Journal of Scientific Research and Management (IJSRM), 2016)
There is growing concern with the growth and prevalence of stress among teachers. In most schools, autocratic administration and supervision appear to be the rule rather than the exception. Recent estimates suggest that teachers in Kenya are so demoralized, despised, frustrated and ridiculed that 30 to 40 per cent of them do not enjoy optimum health while 45 per cent experience occupational tedium. It is against this background that this study investigated the relationship between leader behaviour and experienced role stress among primary school teachers in Nyanza province. Given that most studies have been conducted in industrial settings, this study hopes to fill this gap by deeply exploring incidences of role stress in educational settings within the Kenya context and suggest remedies for mitigating it. The Ex-post facto research design was used to establish the relationship between the independent and dependent variables in the study. Purposive and stratified random sampling techniques were used to select the study sample. The population of the study was 399 primary school teachers drawn from 32 primary schools and 8 District Quality Assurance and Standards Officers (DQASOs) in Nyanza province. Data was collected by means of both structured and unstructured questionnaires and in-depth interviews. Data analysis was performed using the Statistical Package for the Social Sciences (SPSS) Version 16.0. The two tailed t-test and product-moment coefficient of correlation were run to establish the differences and relationships between the independent and dependent variables. The level of significance was set at 0.05. Content analysis of the written free responses was also carried out. It was established that primary school teachers in Nyanza province experience high levels of role stress. It is recommended that individual teachers, educational management personnel, planners and policy makers should have an informed understanding of role stress and its early warning signs hence equip themselves with skills, abilities, behaviours, conflict management and resolution policies and strategies needed to minimize incidences of role stress